Pepper mild mottle virus: a formidable foe of capsicum production—a review - Kumari, Nidhi; Sharma, Vivek; Patel, Priyankaben; Sharma, P. N. (Frontiers in Virology, 2023)
Viruses are one of the major restraining factors to pepper cultivation globally. Among different viruses, Pepper mild mottle virus (PMMoV) is one of the most detrimental plant viruses infecting Capsicum spp. belonging to the genus Tobamovirusand Virgaviridae family has monopartite positive sense single-stranded RNA genome of 6.35 kb size. On an average, PMMoV results in 15-40% losses in capsicum fruit yield. However, the incidence of PMMoV can reach as high as 95%, leading to substantial yield losses ranging from 75% to 95%. The virus is transmitted via contact, soil, and seeds, rather than through insect vectors. The PMMoV is now of worldwide occurrence because of its seed-borne nature. PMMoV mainly infects Capsicum spp. under natural conditions; however, it can experimentally be transmitted to other plants species belonging to families Solanaceae, Cucurbitaceae, Labiatae, Chenopodiaceae, and Plantaginaceae. The resistance to tobamoviruses in capsicum is conferred by L locus. Mutations in the coat protein of PMMoV are responsible for the emergence of L-mediated resistancebreaking pathotypes. The highly contagious nature of the virus, seed transmission behavior, and the emergence of virulence complicate its management through a single approach. Therefore, efforts are directed towards providing a more practical and efficient integrated management solution using the RNA interference approach, exploitation of the L gene for resistance breeding, inhibitory potential of natural products and systemic resistance-inducing antagonistic bacteria as well as chemically synthesized silver nanoparticles. Markers linked to L alleles have been identified to accelerate capsicum breeding programs through marker-assisted selection. Here, attempt has been made to compile the recent developments in PMMoV biology, pathogenic variability, genomic organization, and management strategies.